2018
DOI: 10.1111/vsu.12906
|View full text |Cite
|
Sign up to set email alerts
|

Transsphenoidal surgery: accuracy of an image‐guided neuronavigation system to approach the pituitary fossa (sella turcica)

Abstract: Using the Brainsight neuronavigation system for localization during transsphenoidal hypophysectomy may decrease morbidity and surgical time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
(85 reference statements)
1
21
0
Order By: Relevance
“…In addition, Owen et al reported that an accurate TSS approach to the pituitary fossa was possible by using a neuronavigation system. 31…”
Section: B Amentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Owen et al reported that an accurate TSS approach to the pituitary fossa was possible by using a neuronavigation system. 31…”
Section: B Amentioning
confidence: 99%
“…30 Furthermore, recent reports have indicated an accurate surgical approach that uses a neuronavigation system in TSS operations for canines as well. Even in cases where complete removal of the tumor was usually difficult, increases in operation safety and complete removal rates can be expected 31 [ Figure 8]. In small animal clinical practice, all operations have a learning curve and surgeons improve their operation performance with experiences.…”
Section: Neurosurgical Procedural Skillmentioning
confidence: 99%
“…Precisely locating these structures can prevent injuries to them, thereby decreasing the frequency of perioperative complications. T. J. Owen also reported that using the neuronavigation system for localization, the rostral and caudal margins of the pituitary fossa during TSS may decrease morbidity and surgical time ( 26 ). Doppler ultrasonography has also been shown to determine the exact location of the ICA and whether an aneurysm exists, thereby avoiding injuring the ICA during surgery ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Precisely location these structures can prevent to injuries them, thereby decrease the frequency of perioperative complications. T. J. Owen also reported that using the neuronavigation system for localization the rostral and caudal margins of the pituitary fossa during TSS may decrease morbidity and surgical time (27). Doppler ultrasonography also has been shown to determine the exact location of the ICA and whether it exist an aneurysm, thereby avoid to injury ICA the during surgery (28).…”
Section: Perioperative Complicationsmentioning
confidence: 99%